2013
DOI: 10.1371/journal.pone.0059276
|View full text |Cite
|
Sign up to set email alerts
|

Outer Membrane Vesicles Derived from Escherichia coli Up-Regulate Expression of Endothelial Cell Adhesion Molecules In Vitro and In Vivo

Abstract: Escherichia coli, as one of the gut microbiota, can evoke severe inflammatory diseases including peritonitis and sepsis. Gram-negative bacteria including E. coli constitutively release nano-sized outer membrane vesicles (OMVs). Although E. coli OMVs can induce the inflammatory responses without live bacteria, the effect of E. coli OMVs in vivo on endothelial cell function has not been previously elucidated. In this study, we show that bacteria-free OMVs increased the expression of endothelial intercellular adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 39 publications
1
44
0
1
Order By: Relevance
“…52), tissue factor, thrombomodulin, and the adhesion molecules P-selectin and E-selectin 53 by human endothelial cells, which leads to the recruitment of proinflammatory leukocytes, platelet aggregation and coagulation 52 . Similarly, E. coli OMVs upregulate the expression of E-selectin, ICAM1 and vascular cell adhesion molecule 1 (VCAM1) on the surface of human microvascular endothelial cells 54 . When administered intraperitoneally to mice, these OMVs induce neutrophil aggregation in the lung endothelium in an ICAM1-and TLR4-dependent manner, suggesting that OMVs are used by pathogens to sequester leukocytes in the endothelium 54 .…”
Section: Endothelial Cells and Omvsmentioning
confidence: 99%
“…52), tissue factor, thrombomodulin, and the adhesion molecules P-selectin and E-selectin 53 by human endothelial cells, which leads to the recruitment of proinflammatory leukocytes, platelet aggregation and coagulation 52 . Similarly, E. coli OMVs upregulate the expression of E-selectin, ICAM1 and vascular cell adhesion molecule 1 (VCAM1) on the surface of human microvascular endothelial cells 54 . When administered intraperitoneally to mice, these OMVs induce neutrophil aggregation in the lung endothelium in an ICAM1-and TLR4-dependent manner, suggesting that OMVs are used by pathogens to sequester leukocytes in the endothelium 54 .…”
Section: Endothelial Cells and Omvsmentioning
confidence: 99%
“…When endothelial cells are exposed to these vesicles, they demonstrate an acute inflammatory response by upregulating expression of the endothelial cell adhesion molecules E-selectin, intercellular adhesion molecule-1, and vascular cell adhesion molecule-1. 44 …”
Section: The Potential Role Of the Microbiome In Pulmonary Hypertensionmentioning
confidence: 99%
“…Therefore, OMV, similar to eukaryotic exosomes/microvesicles, are an efficient inter-cellular communication mechanism (Demuth et al, 2003; Galka et al, 2008; Kesty et al, 2004). Previous studies showed that purified OMV are immunostimulatory (Kim et al, 2013; Park et al, 2010), and OMV-associated peptidoglycan has been shown to activate NOD signaling and NF-κB activation (Bonham and Kagan, 2014; Kaparakis et al, 2010). Furthermore, OMV produced by gut microbiota play an immunomodulatory role in mucosal immunity (Hickey et al, 2015; Shen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%